Trees and Seedlings Fungi / Noor Susilawati Mohamad - Mohamad, Noor Susilawati (2004)
This is a study of trees and seedlings fungi. There are four main classes of the fungi, Ascomycota, Deuteromycota, Basidiomycota and Oomycota. There are varieties of diseases cause by fungi. When a tree has a disease, there are many other factors that contribute to stress the tree, thus allowing the disease organisms to enter and spread within the tree. Some major forest diseases are Hypoxylon canker, blister rust, Dutch elm disease, root rot and jarrah dieback. Some of the seedlings diseases are damping off, Fusarium root rots, gray mold, Phytophthora root rots and Rhizina root rots. Good cultural practices and tree care is essential in keeping a strong and healthy trees.